Susceptibility of Staphylococcus aureus to Anti-Inflammatory Drugs with a Focus on the Combinatory Effect of Celecoxib with Oxacillin In Vitro - Okpala, Onyedika Emmanuel; Rondevaldova, Johana; Osei-Owusu, Hayford; Kudera, Tomas; Kokoskova, Tersia; Kokoska, Ladislav (Molecules (Basel, Switzerland), 2024)
Musculoskeletal infections (MIs) are among the most difficult-to-treat staphylococcal diseases due to antibiotic resistance. This has encouraged the development of innovative strategies, such as combination therapy, to combat MI. The aim of this study was to investigate the in vitro antistaphylococcal activity of anti-inflammatory drugs and the combined antimicrobial effect of celecoxib and oxacillin. The minimum inhibitory concentrations (MICs) of 17 anti-inflammatory drugs against standard strains and clinical isolates of S. aureus, including methicillin-resistant strains (MRSAs), were determined using the broth microdilution method. The fractional inhibitory concentration indices (FICIs) were evaluated using checkerboard assays. Celecoxib produced the most potent antistaphylococcal effect against all tested strains (MICs ranging from 32 to 64 mg/L), followed by that of diacerein against MRSA3 and MRSA ATCC 33592 (MIC 64 mg/L). Several synergistic effects were observed against the tested S. aureus strains, including MRSA (FICI ranging from 0.087 to 0.471). The strongest synergistic interaction (FICI 0.087) was against MRSA ATCC 33592 at a celecoxib concentration of 2 mg/L, with a 19-fold oxacillin MIC reduction (from 512 to 26.888 mg/L). This is the first report on the combined antistaphylococcal effect of celecoxib and oxacillin. These findings suggest celecoxib and its combination with oxacillin as perspective agents for research focused on the development of novel therapies for MI caused by S. aureus. This study further indicates that celecoxib could resensitize certain MRSA strains, in some cases, to be susceptible to β-lactams (e.g., oxacillin) that were not previously tested. It is essential to mention that the in vitro concentrations of anti-inflammatory drugs are higher than those typically obtained in patients. Therefore, an alternative option for its administration could be the use of a drug delivery system for the controlled slow release from an implant at the infection site.
Keywords: Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; Celecoxib; antiflogistika; antistaphylococcal synergistic effect; musculoskeletal infections; Staphylococcal Infections; methicillin-resistant S. aureus; oxacilin; Drug Synergism; stafylokokové infekce; Microbial Sensitivity Tests; Staphylococcus aureus; antibacterial activity; non-steroidal anti-inflammatory drugs; synergismus léků; Anti-Inflammatory Agents; Humans; celekoxib; antibakteriální látky; methicilin rezistentní Staphylococcus aureus; mikrobiální testy citlivosti; Oxacillin; lidé